Comprehensive reaction mechanism for n-butanol pyrolysis and combustion - Harper, Michael R.; Van Geem, Kevin M.; Pyl, Steven P.; Marin, Guy B.; Green, William H. (Combustion and flame, 2011)
A detailed reaction mechanism for n-butanol, consisting of 263 species and 3381 reactions, has been generated using the open-source software package, Reaction Mechanism Generator (RMG). The mechanism is tested against recently published data – jet-stirred reactor mole fraction profiles, opposed-flow diffusion flame mole fraction profiles, autoignition delay times, and doped methane diffusion flame mole fraction profiles – and newly acquired n-butanol pyrolysis experiments with very encouraging results. The chemistry of butanal is also validated against autoignition delay times obtained in shock tube experiments. A flux and sensitivity analysis for each simulated dataset is discussed and reveals important reactions where more accurate rate constant estimates were required. New rate constant expressions were computed using quantum chemistry and transition state theory calculations. Furthermore, in addition to comparing the proposed model with the eight datasets, the model is also compared with recently published n-butanol models for three of the datasets. Key differences between the proposed model and the published models are discussed.